Peginterferon Alfa-2a, lamivudine, and the combination for HBeAg-positive chronic hepatitis B - Lau G.K.K. (2014)
BACKGROUND: Current treatments for chronic hepatitis B are suboptimal. In the search for improved therapies, we compared the efficacy and safety of pegylated interferon alfa plus lamivudine, pegylated interferon alfa without lamivudine, and lamivudine alone for the treatment of hepatitis B e antigen (HBeAg)-positive chronic hepatitis B. METHODS: A total of 814 patients with HBeAg-positive chronic hepatitis B received either peginterferon alfa-2a (180 μg once weekly) plus oral placebo, peginterferon alfa-2a plus lamivudine (100 mg daily), or lamivudine alone. The majority of patients in the study were Asian (87 percent). Most patients were infected with hepatitis B virus (HBV) genotype B or C. Patients were treated for 48 weeks and followed for an additional 24 weeks. RESULTS: After 24 weeks of follow-up, significantly more patients who received peginterferon alfa-2a monotherapy or peginterferon alfa-2a plus lamivudine than those who received lamivudine monotherapy had HBeAg seroconversion (32 percent vs. 19 percent [P<0.001] and 27 percent vs. 19 percent [P=0.02], respectively) or HBV DNA levels below 100,000 copies per milliliter (32 percent vs. 22 percent [P=0.01] and 34 percent vs. 22 percent [P=0.003], respectively). Sixteen patients receiving peginterferon alfa-2a (alone or in combination) had hepatitis B surface antigen (HBsAg) seroconversion, as compared with 0 in the group receiving lamivudine alone (P=0.001). The most common adverse events were those known to occur with therapies based on interferon alfa. Serious adverse events occurred in 4 percent, 6 percent, and 2 percent of patients receiving peginterferon alfa-2a monotherapy, combination therapy, and lamivudine monotherapy, respectively. Two patients receiving lamivudine monotherapy had irreversible liver failure after the cessation of treatment - one underwent liver transplantation, and the other died. CONCLUSIONS: In patients with HBeAg-positive chronic hepatitis B, peginterferon alfa-2a offers superior efficacy over lamivudine, on the basis of HBeAg seroconversion, HBV DNA suppression, and HBsAg seroconversion. Copyright © 2005 Massachusetts Medical Society. All rights reserved.